Modeling, Aerodynamic and Crash Simulation on Car Using Fluient (International Journal of Innovative Research in Engineering & Management, 2022)
Aerodynamics plays a crucial role while  designing any automobile components. Due to the  aerodynamics the entire performance of the automotive  will be changed. With an improvement in computer  technology, manufacturers are looking toward  computational fluid dynamics instead of wind tunnel  testing to reduce the testing time and cost. In this paper a  car model considered and it is modeled using solid works  modeling software. The car material is stainless steel. The lift and drag of production vehicle are determined by the  analysis of flow of air around it using Ansys. The  aerodynamic analysis of the design parameter of car will  be performed by using a suitable turbulence model and to  compare the drag coefficient of design of car model by  using CFD software result and experimentally result and  the results will be validated by CFD  analysis/experimental studies. The result of software  analysis has agreed excellently with field experimentally  results. The aerodynamic and crash analysis on car with  of material Al 6061&AISI 4130 with wall and vehicle is  considered The given model is tested under frontal  collision conditions and the resultant deformation and  stresses are determined with respect to a time of 80 Mille  sec for ramp loading using ANSYS software. The crash  analysis simulation and results can be used to assess both  the crashworthiness of current frame and to investigate  ways to improve the design. This type of simulation is an  integral part of the designcycle and can reduce the need  for costly destructive testing program.
Keywords: CAD; CFD; Pro-E; Drag Coefficient; Drag Force; Aerodynamic; ANSYS; Crash